Research and Critical Review of Karunai Literature (Unpublished Poetic Material) in Peshawar - Ishaq, Muhammad; Khalil, Sadia; Saddique, (sourcecoder, 2022)
The COVID-19 pandemic, an unprecedented tragedy that has cast its shadow over both the Eastern and Western societies, has not only disrupted social structures but has also left an indelible mark on the realm of literature and poetry. Amid this trying period, writers in Peshawar grappled with this profound tragedy, seeking to capture its essence through poetry. Regrettably, much of this poignant verse remains confined to the realm of the unpublished, its powerful impact yet to grace the printed page. This research delves into the hitherto undiscovered body of poetic work from Peshawar, which addresses the far-reaching consequences of the pandemic. It brings to the forefront a significant poetic trend, showcasing how these poets meticulously observed and encapsulated the realities of the pandemic in their verses. The prevalent sentiment in this poetry is one of human vulnerability, portraying the poets of Peshawar as keen witnesses to the pandemic's effects, adeptly translating them into verse that resonates with the palpable fear and helplessness that permeated society during these trying times.